1994
DOI: 10.1029/94gl00180
|View full text |Cite
|
Sign up to set email alerts
|

A 27‐month periodicity in the low latitude geomagnetic field and its connection to the stratospheric QBO

Abstract: Geomagnetic daily variations are produced at a height of about 100 to 130 km due to dynamo action of thermospheric winds in combination with the ionospheric conductivity. They are influenced by longterm variability of thermospheric dynamics and are used as tool for investigating a QBO in thermospheric winds. Power spectrum analysis has been applied to monthly means of the daily range of the geomagnetic field. In addition to an annual modulation (and subharmonics) there is clear evidence for a sharp peak at abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Similarly, the quasi‐biennial oscillation (QBO) in the stratosphere and mesosphere has some influence on tidal propagation [ Hagan et al , ; Xu et al , ]. Indeed, Olsen [] and Jarvis [, ] reported small but significant QBO signatures in the S variation. The effect of ENSO and QBO on the lunar tide, however, has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the quasi‐biennial oscillation (QBO) in the stratosphere and mesosphere has some influence on tidal propagation [ Hagan et al , ; Xu et al , ]. Indeed, Olsen [] and Jarvis [, ] reported small but significant QBO signatures in the S variation. The effect of ENSO and QBO on the lunar tide, however, has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a signature of the quasi biennial oscillation exists in the amplitude of the semidiurnal geomagnetic variation at the equator (Olsen, 1994) and at a range of other latitudes (Jarvis, 1996(Jarvis, , 1997. Kohsiek et al (1995) reported 10-and 16-day oscillations, indicative of planetary wave action associated with natural resonances or Rossby normal modes of the atmosphere (Salby, 1984), in geomagnetic data from two mid-latitude stations in the northern hemisphere.…”
Section: Background To Techniquementioning
confidence: 98%
“…For instance, ionospheric foF2 at two stations was found to highly correlate with ENSO (Pedatella and Forbes 2009). The equatorial electrojet and ionospheric foF2, hmF2 were found to oscillate at periods around 26-27 months, which was attributed to the influence of the stratospheric QBO (Olsen 1994;Kane 1995). Since the thermosphere is closely coupled to the ionosphere, it is interesting to examine whether the thermosphere bears imprints of ENSO and QBO as well.…”
Section: Introductionmentioning
confidence: 99%